2017
DOI: 10.1161/atv.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation on Design, Execution, and Reporting of Animal Atherosclerosis Studies: A Scientific Statement From the American Heart Association

Abstract: Abstract-Animal studies are a foundation for defining mechanisms of atherosclerosis and potential targets of drugs to prevent lesion development or reverse the disease. In the current literature, it is common to see contradictions of outcomes in animal studies from different research groups, leading to the paucity of extrapolations of experimental findings into understanding the human disease. The purpose of this statement is to provide guidelines for development and execution of experimental design and interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
224
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(229 citation statements)
references
References 275 publications
4
224
1
Order By: Relevance
“…Furthermore, the hepatocytes size in CPO group was smaller than HPO and EAO groups and those in EAO group was bigger than HPO group. Previous studies have shown that squalene, tocopherols, and polyphenols could improve hepatic steatosis and correct atherosclerosis (Chang, Peng, Yeh, Kao, & Wang, ; Cheng et al., ; Daugherty, Tall, Mjap, Falk, & Fishe, ; Eun‐Young et al., ; Lavine et al., ). These indicated that bioactive compounds in CPO, HPO, and EAO may answer for these results.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hepatocytes size in CPO group was smaller than HPO and EAO groups and those in EAO group was bigger than HPO group. Previous studies have shown that squalene, tocopherols, and polyphenols could improve hepatic steatosis and correct atherosclerosis (Chang, Peng, Yeh, Kao, & Wang, ; Cheng et al., ; Daugherty, Tall, Mjap, Falk, & Fishe, ; Eun‐Young et al., ; Lavine et al., ). These indicated that bioactive compounds in CPO, HPO, and EAO may answer for these results.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a recently published proteomics analysis of EV from poorly characterized BM‐derived MSC‐EVs identified most of the signature proteins, only missing HBB . With porcine models as the goal standard model for cardiovascular research, it is important to note that, based on the two included porcine datasets, the MSC‐EV proteome signature is highly conserved in pigs, underscoring the use of such models for translational research. Besides the identification of most hallmark proteins in all MSC‐EV datasets, the presence of these proteins in non‐MSC‐EV samples was investigated to identify the uniqueness of these proteins for MSC‐EV samples.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used aortic roots to quantify atherosclerotic lesions and aortic arches for differential mRNA expression. In accordance with the American Heart Association statement22, 24 frozen sections (6 μm) were cut from the aortic sinus, the region where the valve or valve cusps first become visible to where the left and right coronary arteries branch off 25. To assess atherosclerosis, Oil Red O‐stained atherosclerotic lesions at aortic sinus (6 sequential sections at 80‐μm intervals) were used to measure both total intimal lesion areas and Oil Red O‐stained lipid deposition areas as described before 20.…”
Section: Methodsmentioning
confidence: 94%
“…Atherosclerosis develops in aortic roots and other vascular beds in hyperlipidemic ApoE‐KO mice, and aortic roots are most common regions for atherosclerosis assessment22 and atherosclerosis assessed at aortic roots correlate highly with those measured in the entire aorta 23. In this study, we used aortic roots to quantify atherosclerotic lesions and aortic arches for differential mRNA expression.…”
Section: Methodsmentioning
confidence: 99%